Success Despite Barriers: Innovative Housing Options for Homeless Young Adults. - Agnese, Kelly.; Golden, Kate.; Tyson, Jen. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: New England Network for Child, Youth and Family Services.